Web security: a whitehat perspective - Hanqing, Wu (CRC Press, 2014)
"This book introduces nearly all aspects of web security. It reveals how hackers work and explains why companies of different scale should choose their own methodology of security. With in depth analysis of the reasons behind the choices, the book covers client script security, server applications security, and Internet company security operations. It also includes coverage of browser security, cross sites script attacks, click jacking, HTML5/PHP security, injection attacks, authentication, session management, access control, web frame security, DDOS, leaks, Internet transactions security, security development lifecycle, and security operations. "--